Physical and mental illness comorbidity among individuals with frequent self-harm episodes: A mixed-methods study - Sadath, Anvar; Troya, M. Isabela; Nicholson, Sarah; Cully, Grace; Leahy, Dorothy; Ramos Costa, Ana Paula; Benson, Ruth; Corcoran, Paul; Griffin, Eve; Phillip, Eunice; Cassidy, Eugene; Jeffers, Anne; et al. (Frontiers in Psychiatry, 2023)
Background Research has indicated an increased risk of self-harm repetition and suicide among individuals with frequent self-harm episodes. Co-occurring physical and mental illness further increases the risk of self-harm and suicide. However, the association between this co-occurrence and frequent self-harm episodes is not well understood. The objectives of the study were (a) to examine the sociodemographic and clinical profile of individuals with frequent self-harm (regardless of suicidal intent) episodes and, (b) the association between physical and mental illness comorbidity, self-harm repetition, highly lethal self-harm methods, and suicide intent. Methods The study included consecutive patients with five or more self-harm presentations to Emergency Departments across three general hospitals in the Republic of Ireland. The study included file reviews (n = 183) and semi-structured interviews (n = 36). Multivariate logistic regression models and independent samples t-tests were used to test the association between the sociodemographic and physical and mental disorders comorbidity on highly lethal self-harm methods and suicidal intent, respectively. Thematic analysis was applied to identify themes related to physical and mental illness comorbidity and frequent self-harm repetition. Findings The majority of individuals with frequent self-harm episodes were female (59.6%), single (56.1%), and unemployed (57.4%). The predominant current self-harm method was drug overdose (60%). Almost 90% of the participants had history of a mental or behavioral disorder, and 56.8% had recent physical illness. The most common psychiatric diagnoses were alcohol use disorders (51.1%), borderline personality disorder (44.0%), and major depressive disorder (37.8%). Male gender (OR = 2.89) and alcohol abuse (OR = 2.64) predicted the risk of a highly lethal self-harm method. Suicide intent was significantly higher among those with a diagnosis of major depressive disorder (t = 2.43; p = 0.020). Major qualitative themes were (a) the functional meaning of self-harm (b) self-harm comorbidity (c) family psychiatric history and (d) contacts with mental health services. Participants described experiencing an uncontrollable self-harm urge, and self-harm was referred to as a way to get relief from emotional pain or self-punishment to cope with anger and stressors. Conclusion Physical and mental illness comorbidity was high among individuals with frequent self-harm episodes. Male gender and alcohol abuse were associated with highly lethal self-harm methods. The mental and physical illness comorbidity of individuals with frequent self-harm episodes should be addressed via a biopsychosocial assessment and subsequent indicated treatment interventions.